2017
DOI: 10.1111/cjag.12160
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Crop Diversification on Rural Poverty in Nepal

Abstract: Crop diversification into high‐value crops (HVCs) can be an important strategy to augment income, generate employment, and reduce poverty in developing countries. We study the impact of crop diversification (share of production value obtained from the HVCs) on household (HH) welfare measures in Nepal. We use three rounds of the nationally representative Nepal Living Standard Surveys: NLSS I (1994/95), NLSS II (2004/05), and NLSS III (2010/11). The dose–response function, propensity score matching, and instrume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 17 publications
1
18
0
Order By: Relevance
“…Von Braun et al () analysed the diversification into vegetable production (snow peas, broccoli, cauliflower, parsley) for the export market by traditional small‐scale farmers in the Western Highlands of Guatemala and discovered that household expenditure, a proxy for income, increased by 33%, moving the poorest upward on the income scale. Thapa, Kumar, Roy, and Josh () estimated that in Nepal, households growing high‐value crops such as vegetables, fruits, and spices or condiments had a mean monthly per capita expenditure 28% higher, on average, than non‐growing farming households, and that high‐value crop growers had a headcount ratio 9% lower than nongrowers. Mukherjee (), however, found that the aggregate per capita net earnings from cultivation of high‐value crops in West Bengal in India was lower in the more diversified villages and that farmers in these villages ended up with considerably less income compared with farmers in the less diversified villages.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Von Braun et al () analysed the diversification into vegetable production (snow peas, broccoli, cauliflower, parsley) for the export market by traditional small‐scale farmers in the Western Highlands of Guatemala and discovered that household expenditure, a proxy for income, increased by 33%, moving the poorest upward on the income scale. Thapa, Kumar, Roy, and Josh () estimated that in Nepal, households growing high‐value crops such as vegetables, fruits, and spices or condiments had a mean monthly per capita expenditure 28% higher, on average, than non‐growing farming households, and that high‐value crop growers had a headcount ratio 9% lower than nongrowers. Mukherjee (), however, found that the aggregate per capita net earnings from cultivation of high‐value crops in West Bengal in India was lower in the more diversified villages and that farmers in these villages ended up with considerably less income compared with farmers in the less diversified villages.…”
Section: Resultsmentioning
confidence: 99%
“…This author also observed that in areas with difficult conditions to build irrigation infrastructure, small farmers (<0.5 ha and 0.5–1 ha) were more likely to produce fruits, oilseeds, jute, and fibres, compared with those from districts endowed with irrigation facilities, in order to meet their cash needs. Thapa et al () estimated a positive correlation between household access to irrigation and the adoption of high‐value crops in Nepal.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Paddy is the most important crop in Nepal, accounting for 35% of gross cropped area (GCA) and 42% of the value of output of the crop sector (Thapa et al 2017). Yet only about 15% of farmers use improved seed (CBS 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Thapa et al, [13], indicated the impact of crop diversifi cation on the measurement of household welfare regarding highvalue crops (HVCs) based on the production assessment. In addition HVCs has better impact on the reduction of poverty and signifi cant increase of per capita income.…”
Section: Literature Reviewmentioning
confidence: 99%